Alexithymia and Psychological Distress in Patients With Fibromyalgia and Rheumatic Disease - Marchi, Laura; Marzetti, Francesca; Orrù, Graziella; Lemmetti, Simona; Miccoli, Mario; Ciacchini, Rebecca; Hitchcott, Paul Kenneth; Bazzicchi, Laura; Gemignani, Angelo; Conversano, Ciro (Frontiers in Psychology, 2019)
Background: Fibromyalgia syndrome (FMS) is a chronic rheumatologic disease characterized by widespread musculoskeletal pain and other psychopathological symptoms which have a negative impact on patients' quality of life. FMS is frequently associated with alexithymia, a multidimensional construct characterized by difficulty in identifying feelings (DIF) and verbally communicating them (DDF) and an externally oriented cognitive thinking style (EOT). The aim of the present study was to investigate the relationship between alexithymia, negative affective states and pain. Method: The sample consisted of 127 participants (M= 25, F=102; mean age: 51.97; SD: 11.14), of which 48 with FMS, 41 with rheumatic diseases (RD) and 38 healthy control group (HC). All groups underwent to a test battery investigating anxiety and depressive symptoms (HADS), pain (VAS; QUID-S /-A) and alexithymia (TAS-20). Results: A high prevalence of alexithymia (TAS ≥ 61) was found in FMS (47,9%) and RD (41,5%) patients, compared to the HC group (2,6%). FMS patients showed significant higher scores than HC on DIF, DDF, EOT, anxiety and depression. The clinical sample, FMS and RD groups combined (N=89), alexithymic patients (AL, N=40) exhibited higher scores in pain and psychological distress compared to non alexithymic patients (N-AL, N=34). Regression analysis found no relationship between alexithymia and pain in AL, meanwhile pain intensity was predicted by anxiety in N-AL. Conclusions: While increasing clinical symptoms (pain intensity and experience, alexithymia, anxiety and depression) in patients with fibromyalgia or rheumatic diseases, correlations were found on the one side, between alexithymia and psychological distress, on the other side, between pain experience and intensity. Meanwhile, when symptoms of psychological distress and alexithymia were subthreshold, correlations with pain experience and intensity became stronger.